T-cell Receptor (TCR) Phenotype of Nodal Epstein-Barr Virus (EBV)-positive Cytotoxic T-cell Lymphoma (CTL). (April 2015) - Kato, Seiichi; Asano, Naoko; Miyata-Takata, Tomoko; Takata, Katsuyoshi; Elsayed, Ahmed Ali; Satou, Akira; Takahashi, Emiko; Kinoshita, Tomohiro; Nakamura, Shigeo
<x xml:space="preserve">Abstract</x> Among Epstein-Barr virus (EBV)-positive cytotoxic T/NK-cell lymphoma, there are only a few reports on the clinicopathologic features of patients with primary nodal presentation (nodal EBV+ cytotoxic T-cell lymphoma [CTL]). Here, we compared the clinicopathologic profiles of 39 patients with nodal EBV+ CTL with those of 27 cases of "extranasal" NK/T-cell lymphoma of nasal type (ENKTL), especially addressing their T-cell receptor (TCR) phenotype. Histologically, 22 of 39 nodal EBV+ CTL cases (56%) were unique in having centroblastoid appearance, which was contrasted with the lower incidence of this feature in ENKTL (15%, P=0.001). In contrast, pleomorphic appearance was more frequently seen in ENKTL than in nodal EBV+ CTL (67% vs. 23%, P=0.001). Thirty-three of 39 nodal EBV+ CTL cases (85%) were of T-cell lineage on the basis of TCR expression and/or TCRγ gene rearrangement; in detail, 18 cases (46%) were TCRβ positive (αβ T), 5 (13%) were TCRγ and/or δ positive (γδ T), and 10 (26%) were TCR-silent type with clonal TCRγ gene rearrangement but no expression of TCRβ, γ, or δ. These results were clearly contrasted by a lower incidence of T-cell lineage in ENKTL (7 cases, 26%, P<0.001). Notably, the survival time of the 5 nodal lymphoma patients with γδ T-cell phenotype was within 3 months, which was inferior to those of αβ T and TCR-silent types (P=0.003), and 3 of those with available clinical information were all found to be associated with autoimmune diseases. These data suggest that nodal EBV+ CTL is distinct from ENKTL.